Da partilha da previdência privada na dissolução do casamento ou da união estável - Lippi, Iris Pedrozo (2010)
The right encompassed in distribution of estate related to private pension plans in an inter vivos dissolution of a marriage or stable union is the chosen topic, with the objective of analyzing the nature of the institution, further to the possibility of its being integrated to the family estate on account of the possibility of its having been an acquisition at some cost during the period the couple was living together, as well as its apportionment in order to fit it to the constitutional principles for family court. For such, four core topics shall be analyzed, the first of which will be referent to Civil Rights in the Constitution whose Magna Carta principles shall guide the construction of an interpretational doctrine of the infra-constitutional legislation. The second topic shall deal with the family s socio-economic evolution, going deeper into new property , further to dealing with private pension plans for its core theme. The third topic deals with the legislation s approach to the distribution of assets acquired at some cost by the couples during their marriage or stable unions, further to cases where there would be a possibility of dividing the private pension plan between the couple. The fourth topic shall make an approach on manners of performing the apportionment plus factors that may exert some influence over the calculation of parts in the joint property